POSTERIOR FOSSA TUMORS: A CASE REPORT OF ACQUIRED TORTICOLLIS IN CHILDREN - Claudia Sciarrotta (Euromediterranean Biomedical Journal, 2022)
Torticollis is a pathological condition characterized by involuntary flexion of the neck to the affected side and contextually a rotation of the chin in the opposite direction. We present the case of a 7-year-old girl, admitted to the paediatric emergency department complaining of headache, laterocollis rotation, left torticollis and deviation of the head to the right, without history of trauma or systemic illness. Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) brain scans were performed, showing a subtentorial lesion, expanded into the left median and paravermian region, associated with hypertensive hydrocephalus. Histopathological analysis revealed a first-degree astrocytoma. The aim of this case report is to highlight the importance of tumors as the differential diagnosis of acquired torticollis in children.